ChemInform Abstract: Spin Exchange and Magnetic Dipole—Dipole Interactions Leading to the Magnetic Superstructures of MAs2O6 (M: Mn, Co, Ni). Issue 24 (2nd June 2014) - Koo, Hyun‐Joo; Whangbo, Myung‐Hwan
Abstract The spin exchange and magnetic dipole—dipole interaction energies of the isostructural title compounds are evaluated by DFT calculations.